Option repricing, corporate governance, and the effect of shareholder empowerment - Gulen, Huseyin; O'Brien, William J. (Journal of Financial Economics, 2017)
We use the practice of employee option repricing to investigate how shareholder involvement in firm compensation policies affects the quality of firm governance. We find that a 2003 reform that empowered shareholders to approve or reject repricing proposals led to value increases in previous repricers. The likelihood of repricing becomes less sensitive to poor manager performance, but remains similarly sensitive to bad luck, after the reform. Average post-repricing changes in firm performance are positive only after the reform. Overall, our results suggest that shareholder empowerment improves the governance of repricing and can transform repricing into a value-creating tool.